Uprzemysłowienie Ordynacji Zamojskiej w okresie międzywojennym - Kozaczka, Marian (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
In the interwar period, the Zamoyski’s Estate was the biggest private landed estate in Poland. In 1922, there were 58 industrial plants on its 190 279 ha area, including “Klemensów” sugar factory, brewery, wooden goods production plant, and clinker factory. Compared to other landed estates located in the lubelskie province and in Poland, the Zamoyski’s Estate was well industrialized, and its biggest factories could run mass production. The great economic crisis of 1929–1934 together with writing off and land dividing campaign, as well as liquidation of easements had a significant impact on the financial base of the estate. At that time, significant part of the land and numerous factories were separated out of the estate. In the middle of 1939, the area of the Zamoyski’s Estate was 61 095 ha of land with 19 factories located thereon. All factories continued the estate business activity and were important centres offering jobs to a lot of people, and could run diverse production for domestic and foreign markets.